Pengetahuan, Sikap, Peran Teman Sebaya dan Perilaku Seksual Pranikah pada Remaja - Izzulhaq, Lazuardi Nabiel; Ningsih, Wahyu Tri; Nugraheni, Wahyuningsih Triana (Journal of Health Management Research, 2023)
Background:Middle adolescents, who range from 14 to 16 years of age, are characterized by the following features: a need for identity, an emerging need to relieve stress, strong feelings of love, and fantasies of engaging in sexual activity Aims:The aim of the study was to find out how knowledge, attitudes, peer roles and premarital sexual behavior are described in adolescents at SMP Negeri 6 Tuban. Methods:The design of this study was descriptive. The research population was all students of class IX at SMP Negeri 6 Tuban, totaling 242 students. The sample size is 150 students using the Simple Random Sampling technique. Retrieval of data with questionnaires and descriptive analysis using frequency tables. Results:The results showed that the students of SMP Negeri 6 Tuban mostly had good knowledge (75%), while the attitude of the majority still had a negative attitude (63%).Then a small portion of the role of peers play a role in premarital sexual behavior with a percentage (25%). And a small proportion of sexual behavior in adolescents is at serious risk (1%) Conclusion:The more knowledge received the better the students' knowledge so that students can sort out the right information, understand and understand the impact of premarital sexual behavior on adolescents, and believe that the existence of this information will influence the students' personal attitudes which are good too.